Beyond the Lungs—Emerging Challenges in Adult Cystic Fibrosis Care - Mulrennan, Siobhain; Sapru, Karuna; Tewkesbury, Daniel; Jones, Andrew M. (Seminars in Respiratory and Critical Care Medicine, 2022)
Cystic fibrosis (CF) is a multisystem disease. This article provides an up-to-date review of many of the nonrespiratory complications of CF, including mental health issues, nutritional and gastrointestinal problems, fertility issues, diabetes mellitus, bone health and musculoskeletal problems, liver disease, renal problems, and risk of malignancy. It highlights the recent impact of new therapies, including CF transmembrane conductance regulator modulators, on the nonrespiratory complications of CF and provides insights into the potential challenges faced by an aging population of adults with CF and their caregivers, including the potential future risk for cardiovascular disease.
Keywords: cystic fibrosis; CFTR modulators; aging; malignancy; cardiovascular disease; bone health